Strengthening bean seed systems with focus on biofortified bean varieties to respond to bean farmers and market demand in Burundi, Kenya and Rwanda - Pan-Africa Bean Research Alliance (Pan-Africa Bean Research Alliance, 2016)
The seed systems project is funded by the Syngenta Foundation for Sustainable Agriculture (SFSA) and aims at strengthening bean seed systems in three east African countries: Burundi, Kenya and Rwanda with focus on biofortified bean varieties to respond to bean farmers and market demand. To achieve the objectives, project implementation process centers on: (1) identifying bean seed systems innovations linking to other complementary services/linkages; (2) establishing multi-stakeholders platforms with access to inputs and output market; (3) fast tracking release and use of biofortified beans focus but also and few other demands; (4) facilitating licensing of seed companies and creating linkages to crop insurance services providers; (5) enhancing equitable bean seed access; (6) facilitating regional germplasm exchanges; (7) enhancing skills and knowledge in bean agronomy/seed systems – market/demand led breeding; and (8) sharing lessons learnt across countries and scaling up best practices to other countries. This report summarizes the progress made in the project implementation during the period February, 2015 to January 2016.The report is divided into three sections. The first section of the report presents a summary of the technical reports from respective countries. Section two presents a summary of students’ reports; while section three presents highlights on the semi-annual review meeting (organized and facilitated by PABRA), dwelling on remarks by some of the project stakeholders (a detailed report on the semi-annual review meeting has been produced separately).